Deposition-precipitation versus anionic-exchange Au/Al2O3 catalysts: a comparative investigation towards the selective reduction of NOx - Nguyen, D. L.; Shubhangi B. Umbarkar; Dongare, Mohan K.; Lancelot, Christine; Girardon, J. S.; Dujardin, Christophe; Granger, P. (Catalysis Communications, 2012)
Catalytic properties of supported gold catalysts on gamma-Al2O3 prepared by a conventional deposition-precipitation method were compared with those obtained by anionic-exchange for the reduction of NOx by hydrocarbon under lean conditions that simulate Diesel engine exhaust gas. Interestingly, a catalytic activity enhancement is observed after thermal ageing under reactive conditions at 500 degrees C on anionic-exchanged samples which make them suitable for practical developments. On the other hand, the reverse trend is observed on the solids prepared by deposition-precipitation which deactivate at low temperature. Such changes in catalytic properties have been tentatively explained on the basis of textural and structural modifications taking place during thermal ageing under wet atmosphere. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Anionic-exchange; Au catalyst; Deposition-precipitation; NOx abatement; Selective catalytic reduction

One-pot sol-gel preparation for efficient cobalt-molybdenum-titania hydrotreating catalysts - Nguyen, D. L.; Gillot, S.; Souza, D. O.; Blanchard, P.; Lamonier, Carole; Berrier, E.; Kotbagi, T. V.; Dongare, Mohan K.; Shubhangi B. Umbarkar; Cristol, S.; Payen, E.; Lancelot, Christine (Chemcatchem, 2012)
Titania-based hydrodesulfurization catalysts were prepared by using a one-pot solgel method with the titanium peroxo complex as titanium precursor and molybdenum and cobalt precursors dissolved in the aqueous hydrogen peroxide solution used during synthesis. Catalysts with MoO3 loadings varying from 5 to 40 wt?% and a Co/Mo atomic ratio of 0.5 were prepared. Solids with molybdenum loadings below 20 wt?% MoO3 demonstrated poor hydrodesulfurization activity for the model compound thiophene. This was attributed to the presence of a large amount of embedded cobalt and molybdenum species in the titania matrix. A significant increase in the catalytic activity was observed for solids containing 20 and 25 wt?% of MoO3 on which active species appeared to be accessible on the titania surface. Furthermore, the highest conversion obtained on these solgel solids was superior to the highest conversion obtained on reference catalysts prepared through the impregnation of ammonium heptamolybdate and cobalt nitrate on commercial titania.
Keywords: cobalt; heterogeneous catalysis; Molybdenum; sol-gel process; titanium

Rational preparation of Ag and Au bimetallic catalysts for the hydrocarbon-SCR of NOx: sequential deposition vs. coprecipitation method - More, Pavan M.; Nguyen, D. L.; Dongare, Mohan K.; Shubhangi B. Umbarkar; Nuns, N.; Girardon, J. S.; Dujardin, Christophe; Lancelot, Christine; Mamede, Anne-Sophie; Granger, P. (Applied Catalysis B-Environmental, 2015)
This study emphasizes the importance of the preparation method for bimetallic Au-Ag catalysts supported on alumina in the selective reduction of NOx by hydrocarbons with gas feed compositions representative of diesel fuelled engine exhaust gas. An optimal balance between oxidative and reductive surface properties is obtained when Au and Ag are successively introduced. Significant re-dispersion processes take place when the catalyst runs at 500 degrees C leading to a gain in activity at low temperature and ascribed to a better interaction between Au and Ag species. Co-precipitation leads to a preferential formation of intermetallic Au-Ag particles which is detrimental to the catalytic performances. Aging at 500 degrees C leads to a significant particle sintering and a strengthening of the metallic character. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Au-Ag particles; Co-precipitation; DeNO(x) reaction; HC-SCR